Twenty-five-year mortality trends of four major histological subtypes of cervical cancer: a population-based study using the Osaka cancer registry data - Komura, Naoko; Mabuchi, Seiji; Sasano, Tomoyuki; Kamiura, Shoji; Morishima, Toshitaka; Miyashiro, Isao (Frontiers in Oncology, 2023)
Objective: To assess the mortality trends of four major histological subtypes of cervical cancer diagnosed between 1994 and 2018.Methods: This population-based retrospective cohort study was conducted using the Osaka Cancer Registry data from 1994 to 2018. A total of 12,003 patients with cervical cancer, squamous cell carcinoma (SCC), adenocarcinoma (A), adenosquamous cell carcinoma (AS), or small cell neuroendocrine carcinoma (SCNEC) were identified. Patients were classified into groups according to the extent of disease (localized, regional, or distant), year of diagnosis (1994-2002, 2003-2010, or 2011-2018), and histological subtype (SCC, A/AS, or SCNEC). Then, their survival rates were assessed using univariate and multivariate analyses. This is a provisional file, not the final typeset article Results: Overall, improved survival rates were observed according to the year of diagnosis in patients with local, regional, and distant cervical cancers. When examined according to the histological subtypes, improved survival rates according to the year of diagnosis were observed in patients with local, regional, and distant SCCs and in those with local and regional A/AS. In patients with distant A/AS, the survival rates did not improve since 2003. In patients with cervical cancer with SCNEC, the survival rates did not improve since 1994 irrespective of the extent of the disease. In the multivariate analysis, non-SCC histology was found to be an independent prognostic factor for OS.In contrast to SCC histology associated with improved survival between 1994 and 2018, SCNEC histology and advanced (stage IVB) A/AS remain to be the unmet medical needs for the management of cervical cancer.